مكانة الاجتماعية للأسرة و علاقتها بالغش المدرسي دراسة حالة لعينة من طلبة بكلية الطب بجامعة الأغواط - حدباوي راضية; صاني فتحية (My University, 2023)
The study aimed to reveal the Most influential relationship between social status and the phenomenon of school cheating, in addition to revealing whether there is a relationship between the educational and cultural level of parents and the social level of the family in the spread of the phenomenon of school cheating. , using the descriptive approach as it is appropriate for the subject of study. Where the study was conducted on 10 samples of students of the Faculty of Medicine and we chose them randomly, as for the study tools, we used the interview guide and analyzed the respondents' speech through the interview guide containing 3 axes, and the results revealed that: - The family cares more about the success of its children than its social status in society. - The family does not lead its children to cheat for the sake of its social ambitions. - The educational qualifications of the family have nothing to do with the practice of cheating by children, as there are parents who have not obtained a high level of education, but their children are in senior positions without resorting to cheating. The professional qualifications of the family have no role in - the right of children to cheat, as there are parents who are not in a high professional position, but their children have reached .the highest positions with their efforts and perseverance